Impact of Prophylactic Fluoride Agents On the Surface Roughness of Newer orthodontic arch wires - Panda, Suchareeta; M, Anandu; N, Goutham; M, Pavithra Bai; Pani, Saibalini; Rao, Sakesth Rama (Bangladesh Journal of Medical Science, 2024)
Fluorides serve an important part in orthodontic therapy as a prophylactic strategy. However, the harmful effects of fluoride are typically disregarded due to its widespread use as an anti-cariogenic agent in a variety of dental materials. The effects of these fluoride agents on conventional arch wires have been studied extensively but not on newer wires such as coated wires or braided wires. Hence this study was undertaken to assess the effects of prophylactic fluoride agents on the surface properties of non-coated Nickel-Titanium orthodontic wires and compare it with coated esthetic Ni-Ti wires and braided Ni-Ti wire. Materials and methods: In this study, we compared three packages of 270 orthodontic arch wires made of nickel titanium. For the control, the third set of 30 wires was stored in plastic vials containing 5ml of artificial saliva for two months. Subgroup a did not make use of any fluoride treatments. Samples from subgroup b were treated with Phos-flur gel for one minute every day for 2 months, while those from subgroup c were treated with Prevident 5000. An optic profilometer was used to measure the wires roughness. Results: The investigation found that both the acidulated fluoride agent (Phos-flur gel) and neutral fluoride agent (Prevident 5000) had an effect on the surface attributes of all three sets of wires. Coated esthetic Ni-Ti wires showed highest surface roughness followed by braided Ni-Ti wire. Conclusion: The findings of the research showed that using fluoride preventive treatments (such as mouthwash or gels) during orthodontic treatment decreases the arch wires characteristics. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S107-S114